Efficacy of Sodium Valproate and Olanzapine in treating bipolar affective disorder 'mania' at a tertiary care hospital in Nepal: A comparative study (Janaki Medical College Journal of Medical Science, 2017)
Background and Objectives: Bipolar affective disorder, mania is the mood of an abnormally elevated arousal energy level or a state of heightened overall activation with enhanced affective expression together with lability of affect. The objective of the study was to compare the efficacy of sodium valproate and olanzapine in bipolar affective disorder, mania patients at a tertiary care hospital in NepalMaterial and Methods: A randomized observational prospective open label study was conducted for one and half year at College of Medical Sciences-Teaching Hospital (CMS-TH), Bharatpur, Nepal in the Psychiatry Department. Sixty patients diagnosed with bipolar affective disorder, mania were enrolled. 30 patients received sodium valproate and 30 patients received olanzapine. Patients were monitored and evaluated on baseline (day 0), day 7 and day 30 and compared to the baseline for the severity of illness using the 11-item Young Mania Rating Scale (YMRS).Results: The mean baseline YMRS score for all cases on sodium valproate (n=30) on day 0 was 38.87 ± 3.73, while it was reduced to 13.90 ± 1.95 (p < 0.001) on day 30. Similarly, the mean baseline YMRS score for all cases on olanzapine (n=30) on day 0was 40.83 ± 6.50, while it was reduced to 14.47 ± 2.83 (p < 0.001) on day 30.The mean decrease in YMRS score by sodium valproate was 64.24% and by olanzapine was 64.56%.Conclusion: Treatment with sodium valproate and olanzapine significantly improves the mean mania ratings score and there is no statistically significant difference in efficacy of both the drugs in patients diagnosed with bipolar affective disorder, mania.Janaki Medical College Journal of Medical Sciences (2016) Vol. 4(1): 27-35